2017
DOI: 10.15547/tjs.2017.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Caracteristics of productive and quality possibilities of introduced rice varieties grown under conditions of southern Bulgaria

Abstract: The study was conducted during the period 2013-2014. Three Turkish (Denep, Efe, Gala) and four Italian (Baldo, Creso, Roma, Puma) rice variety used in the country are explored. During the growing season it is applied the standard agrotechnics of rice cultivation in Bulgaria.The samples were evaluated on morphological, biochemical and economic qualities according to international descriptors: vegetation period, paddy yield, length of panicle, weight of a panicle, mass of 1000 grains, total number grains in pani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…When growing varieties of Egyptian breeding, it was shown that the methods of sowing seeds and seedlings influenced grain size, yield and milled rice quality [6]. Studies are being conducted on the correlation of quality and yield traits of Turkish varieties under growing conditions in Bulgaria [7]. In India, the quality of yield of rice varieties of various origin grown in saline lands in Tamil Nadu was studied.…”
Section: Introductionmentioning
confidence: 99%
“…When growing varieties of Egyptian breeding, it was shown that the methods of sowing seeds and seedlings influenced grain size, yield and milled rice quality [6]. Studies are being conducted on the correlation of quality and yield traits of Turkish varieties under growing conditions in Bulgaria [7]. In India, the quality of yield of rice varieties of various origin grown in saline lands in Tamil Nadu was studied.…”
Section: Introductionmentioning
confidence: 99%